Hypoxia-Inducible Factor Regulates Endothelial Metabolism in Cardiovascular Disease - Ullah, Karim; Wu, Rongxue (Frontiers in Physiology, 2021)
Endothelial cells (ECs) form a physical barrier between the lumens and vascular walls of arteries, veins, capillaries, and lymph vessels; thus, they regulate the extravasation of nutrients and oxygen from the circulation into the perivascular space and participate in mechanisms that maintain cardiovascular homeostasis and promote tissue growth and repair. Notably, their role in tissue repair is facilitated, at least in part, by their dependence on glycolysis for energy production, which enables them to resist hypoxic damage and promote angiogenesis in ischemic regions. ECs are also equipped with a network of oxygen-sensitive molecules that collectively activate the response to hypoxic injury, and the master regulators of the hypoxia response pathway are hypoxia-inducible factors (HIFs). HIFs reinforce the glycolytic dependence of ECs under hypoxic conditions, but whether HIF activity attenuates or exacerbates the progression and severity of cardiovascular dysfunction varies depending on the disease setting. This review summarizes how HIF regulates the metabolic and angiogenic activity of ECs under both normal and hypoxic conditions and in a variety of diseases that are associated with cardiovascular complications.